KONSEP QIYAS AKAD MUDHARABAH TERHADAP AKAD MUSAQAH - ghazali, Muhammad lathoif; amanda, yudi amirul aji (Universitas Muhammadiyah Surabaya, 2021)
Research aims to understand the concept of qiyas in mudharabah divorce .This research result indicates that mudharabah divorce with musaqah illah have in common, in common can be viewed from the side of understanding, in the manner of the agreement and the cancellation of requirements as the requirements sighat in both the divorce requiring the sighat (ijab and qabul), and there are also requirements and do not all requirements used same it is just in object the division of the gaining of it is that would differ, if not of capital mudharabah used in the form of money, musaqah in the form of a garden, mudharabah used in divorce and financial institution musaqah in use in agribusinesses. In nullification only two point according to researchers under the same one of both the parties that died and things that block the annulment of (crazy or murtad). The practice of akkad mudharabah is as ashl then al-musaqah is as far'u, after we had put together in the same evidence is cooperation between / owners or those with capital manager / the best of garden against the power to keep the business going and then within the division of the gaining of it is divorce agreement has been agreed upon at the beginning. So with this, and not even go near mudharabah musaqah in in business activities.KeywordsÂ : Qiyas, Illat, Mudharabah, MusaqahÂ